Children's Oncology Group's 2013 blueprint for research: Neuroblastoma. Issue 6 (19th December 2012) - Park, Julie R.; Bagatell, Rochelle; London, Wendy B.; Maris, John M.; Cohn, Susan L.; Mattay, Katherine M.; Hogarty, Michael; ,
Abstract Estimated 5‐year survival rates for patients with non‐high‐risk and high‐risk neuroblastoma are 90% and 50%, respectively. Recent clinical trials have shown excellent outcomes with reduced therapy for non‐high‐risk disease. For patients with high‐risk neuroblastoma treated with chemoradiotherapy, surgery, and stem cell transplantation, the addition of anti‐disialoganglioside (GD2) immunotherapy plus cytokines improves survival. Upcoming trials will study the incorporation of targeted radionuclide therapy prior to myeloablative chemotherapy into high‐risk treatment. Phase 2 trials will investigate druggable target(s) including mTOR inhibition and GD2‐directed therapy in combination with chemotherapy for patients with recurrent neuroblastoma, and ALK inhibition for those with ALK‐aberrant tumors. Pediatr Blood Cancer 2013; 60: 985–993. © 2013 Wiley Periodicals, Inc.